THE STUDY OF CHARACTER LEARNING ON DEVELOPMENT OF EMPATHY ATTITUDE AND SOCIAL RESPONSIBILITY IN BOARDING SCHOOL - Endang Sumantri, Lina Agustina Dadang Sundawa (Department of Civic Education, 2016)
In the middle of 1990 were built boarding school having a pattern of education thorough to create educational environment ideal in developing and to create character of students. This study was conducted in junior high school Daarut Tauhiid Boarding School Bandung. This study adopted qualitative approaches and methods of descriptive. Research findings dhow that : Forms an empathy and social care that reflected in learning activities civic education: appreciate a difference of opinion, to cooperate in team discussion, an expression of opinion students over a moral to prioritize the interests of others first .Then, in the program extracurricular namely participating in the activity of gathering funds and social activities. The culture of schools and dormitory the students reflected an empathy and socially responsible by providing aid tending if is sick, provide loans money, motivate have a friend sad, sensitive to problem those who around. Although there is still several things must be repaired next in system learning character in schools that integrated with curriculum based the value of a character in boarding. So, it will more strengthen in developing an empathy and social care awareness students.Keywords : Character Learning, Boarding School, Civic Education, Emphatic Behaviour, Social Care Awareness